The Impact of Monetary Policy on Agricultural Productivity and Food Prices in Nigeria: A Time-Series Analysis - Muhammed, Abdullahi Bashir (African Journal of Stability and Development (AJSD), 2024)
The study examined the impact of monetary policy on agricultural productivity and food prices in Nigeria. The study covered the period of 29 years spanning from 1995 to 2023 which constitutes one hundred and sixteen observations. Data were extracted from the Central Bank statistical bulletin. The estimation technique used was Autoregressive distributed lag (ARDL). The results showed that exchange rates boost Nigeria’s agricultural output and food prices in the short and long term. The estimation showed that interest rates negatively affect agricultural productivity and food prices in Nigeria in the long run but positively affect agricultural sector growth in the short term. The estimation showed that money supply reduces agricultural productivity in the short and long term. However, the estimation showed that money supply impacts food prices positively in the short and long term. It was concluded that exchange rate increases or promotes export-oriented agricultural products but has a side effect on imported food or production input. High interest discourages agricultural technology investment due to higher operating costs, which lowers agricultural productivity and raises food prices. Increased money supply without agricultural investment lowers agricultural productivity and raises food prices. Policymakers should reduce exchange rate fluctuations and create a predictable environment for farmers to invest in productivity-enhancing practices. The government should increase agricultural credit, ensure low-interest loans, and control prices during inflation. To avoid food price inflation and boost agricultural productivity, part of the money supply should go to real sector productivity, particularly agriculture.